Pengembangan Aplikasi Pemesanan PlayStation dengan Integrasi Database MySQL Menggunakan Visual Studio 2022 - Moh. Fairus Heriawan; Marky Cavalera Prasetya; Rizky Basatha (CV. Multi Kreasi Media, 2024)
This PS rental application is designed to simplify the game console rental process using Visual Studio 2022 and MySQL as the database management system. This application allows users to enter renter data, make reservations, and process payments in an efficient and user-friendly manner. With an intuitive interface, users can easily access various features, including tenant and transaction data management. The MySQL database is used to store important information in a structured manner, ensuring data security and ease of access. Through the development of this application, it is expected to improve operational efficiency in game console rental management, as well as provide a better user experience.